Perception of riba among the Muslims in Malaysia: an exploratory study - Fontaine, Rodrigue Ancelot Harvey (IIUM Institute of Islamic Banking and Finance, 2019)
This study explores the perception of Muslims in Malaysia’s about ribā, eating pork, drinking alcohol and dating. A pilot questionnaire was developed. To avoid social desirability, the questionnaire treated respondents as informants. 267 informants responded to the pilot. The Cronbach alpha was 0.743. The questionnaire was improved with the addition of four additional questions. A new questionnaire was answered by 351 informants. The Cronbach alpha increased to 0.78. The findings were compared to similar data collected on the perceptions’ towards eating pork, drinking alcohol and dating. About 31% of Muslims have no problems taking ribā. About 40% of Muslims seem unsure about the legal status of ribā. 55% said that Muslims take ribā from time to time, 48% said that Muslims were forced to take ribā while only 36% found that ribā was the logical thing to do. Only 25% of Muslims believed that ribā would a good thing. Further analysis suggests that there are structural reasons why Muslims take ribā. This author suggests that these findings establish a base-line from which future researchers might understand how sins become culturally acceptable or become culturally unacceptable.